Fluvial connectivity drives carbon cycle dynamics in a tropical mega‐delta - Adrian M. Bass; Wenguang Tang; Andrew C. G. Henderson; Virginia N. Panizzo; James Fielding; Abhra Chanda; Souvik Shil; Tuhin Ghosh; Charlotte Slaymark; Andy Large (Limnology and Oceanography, 2026)
Coastal estuaries are hotspots of biogeochemical cycling, biodiversity, and sediment processing, yet the drivers of carbon cycle processes remain poorly constrained. Here, we elucidate the influence of hydrological connectivity on carbon biogeochemistry in the Indian Sundarban over successive monsoon seasons by comparing hydrologically connected channels with perennial freshwater flow to channels isolated from feeding rivers. Results demonstrate dissolved organic carbon (DOC) and particulate organic carbon (POC) varied significantly with both season and connectivity. Dissolved organic carbon peaked pre‐monsoon and POC during the monsoon, with higher concentrations in hydrologically connected sites. Dissolved inorganic carbon (DIC) declined during the monsoon season but showed no connectivity effect. Elevated DOC relative to conservative mixing was attributed to freshwater runoff or groundwater input. Isotope data (δ 13 C) indicated POC respiration dominated during pre‐ and post‐monsoon, while DOC flocculation during the monsoon controlled POC dynamics, particularly in connected sites. Carbonate dissolution primarily regulated pre‐monsoon DIC, while organic matter degradation dominated in the monsoon and post‐monsoon periods. CO 2 efflux, measured across all sites, was consistently a source to the atmosphere and two to four times higher in connected channels, with higher turbulence driving maximum fluxes. Our findings demonstrate that hydrological connectivity fundamentally structures estuarine carbon cycling, lowering organic carbon concentrations and enhancing CO 2 fluxes. Shifts in global coastal delta sediment dynamics, in association with anthropogenic river management, therefore, have the potential to significantly alter delta carbon dynamics on a global scale.

Toxic tides of change: Ocean pollution as a cultural tipping point - Jessica M. Vandenberg; Eliana Ritts; Yoshitaka Ota; Russell Fielding (Ambio, 2026)
This paper offers a new perspective on the valuation of the impacts of industrial ocean pollution. Rising levels of industrial pollutants have a profound impact on marine resource-dependent peoples, particularly those dependent on seafood consumption. We argue that current regulation of these pollutants is both insufficient and inequitable, as it only accounts for impacts on physical health while ignoring cultural implications. This paper introduces the “cultural tipping point” as a new framework that integrates the impacts of ocean pollution on peoples’ physical and cultural health and well-being. Drawing on anthropology, marine sciences, public health, and critical Indigenous studies, the cultural tipping point synthesizes diverse concepts of “cultural keystone species,” food sovereignty, and industrial pollution. Ultimately, our goal is to make the cultural impacts of ocean pollution legible within global governance networks, and to advocate for greater allocation of societal resources to address this issue.

Recurrent and Non-Recurrent Copy Number Variants in Native Americans and a Cosmopolitan Sample in Relation to Alcohol Use Disorder and Other Psychiatric Diseases - Salma M Wakil; Keita Morisaki; Pei-Hong Shen; Dylan G Sucich; Melanie Schwandt; James Fielding Hejtmancik; Cheryl Marietta; Qiaoping Yuan; Nancy Diazgranados; Colin A Hodgkinson; David Goldman (Molecular Neurobiology, 2026)
Copy number variants (CNVs) can alter disease susceptibility by gene deletion, duplication, and other mechanisms, and have been implicated in neuropsychiatric diseases. However, their rarity or de novo nature impedes linkage analysis. Therefore, we identified recurrent CNVs (rCNVs) in Native Americans with low genetic admixture and high prevalence of alcohol use disorder (AUD) and other psychiatric disorders. Large (> 200 kb) rCNVs were abundant in Plains Indians (PI) and Southwest American Indians (SWI), almost all carrying at least one rCNV, with some CNVs found in both geographically and linguistically distinct tribes. In patients carrying rCNVs, gene deletions led to haploinsufficiency, and duplications led to increased gene dosage. Haplotype analysis revealed a common chromosome 6p21.33 recurrent CNV (rCNV) that persisted in Native Americans for at least 750 generations, leading to haploinsufficiency of at least two genes. Gene-based CNV burden and CNV count did not predict AUD or other psychiatric disorders. However, an rCNV, found in PI and duplicating three genes within the 22q11.2 velocardiofacial syndrome region, showed nominally elevated odds ratios in generalized linear mixed models accounting for kinship as a random effect and age and sex as fixed covariates. For AUD, the odds ratio was 3.19 (95% CI 1.12–9.07, p = 0.03), and for psychiatric diagnosis, the odds ratio was 4.80 (95% CI 1.37–16.82, p = 0.014). These associations, calculated with adjustment for relatedness, did not remain statistically significant after correction for multiple testing, illustrating the challenge of linking CNVs to behavior even if they are recurrent and potentially of large effect. The effects of most CNVs are undetectable via genome-wide association studies with single SNPs, and in cosmopolitan populations, most CNVs are nonrecurrent, sometimes affecting similar genomic regions but differing in their properties, and origins. Recurrent CNVs having ancient origins are prevalent in Native American populations providing an opportunity to examine their relationships to disease risk. However, we observed that neither gene-based CNV burden nor individual rCNVs did not predict AUD or other psychiatric outcomes, after adjustment for the numbers of rCNVs tested.

Navigating challenges in spatio-temporal modelling of Antarctic krill abundance: Addressing zero-inflated data and misaligned covariates - André Victor Ribeiro Amaral; Adam M. Sykulski; Sophie Fielding; Emma Cavan (Spatial Statistics, 2025)

Assessing South Africa’s marine protected area quality and progress towards conservation goals: An application of The MPA Guide framework - Laurel C. Field; Kendyl Wright; Jenna Sullivan-Stack; Jean M. Harris; Stephen P. Kirkman; Peter J. Fielding; Ané Oosthuizen; Siyabonga Dlulisa; Anastasiya Laznya; Emanuel J. Gonçalves; Kirsten Grorud-Colvert (Marine Policy, 2025)

Media ownership and coverage patterns of established, disruptive, and unconventional climate advocacy groups - Robyn E. Gulliver; Xiongzhi Wang; Winnifred R. Louis; Kelly S. Fielding; Rebecca M. Colvin (Climatic Change, 2025)
Groups advocating on climate and environmental issues often seek to obtain media coverage to increase public awareness of their cause, yet comparatively little is understood about the factors influencing the volume and content of that coverage. This study investigates the quantity and characteristics of media coverage of climate advocacy groups through a mixed-method analysis of 17,380 Australian media articles published between 2017–2022. Four types of advocacy groups were the focus: ‘Established’ groups (large professionalised environmental groups); ‘Disruptive’ groups (the greatest use of civil resistance tactics); and two types of what we call ‘Unconventional advocates’ – those who advocate for action on climate change but from a social identity position that is either typically not associated with climate action (‘Role-based unconventional advocates’, such as parents or doctors) or has a history of conflict with climate or other environmental causes and environmentalists (‘Conflict-spanning unconventional advocates’, such as farmers and political conservatives). Findings indicate that linguistic cues associated with conflict, achievement, and emotional sentiment differed significantly according to the advocacy group type and media ownership. While Established groups gained the greatest volume of coverage, Disruptive groups attracted the highest conflict language and lowest achievement language, particularly in outlets published by News Corp (the Murdoch owned media company). Meanwhile, conflict-spanning unconventional advocates received coverage using language with the lowest levels of conflict and highest levels of achievement. Our findings highlight the potential for new types of climate advocates to gain comparative sympathetic media coverage and potentially expand the social basis of support for climate action.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Observations of southern right whales ( Eubalaena australis ) surface feeding on krill in austral winter at South Georgia - Susannah V. Calderan; Tracey Dornan; Sophie Fielding; Ryan Irvine; Jennifer A. Jackson; Russell Leaper; Cecilia M. Liszka; Paula A. Olson; Martin A. Collins (Marine Mammal Science, 2023)

In situ calcite U–Pb geochronology of carbonate and clastic sedimentary rocks from the Canning Basin, Western Australia - Z. Li; K. Rankenburg; L. S. Normore; N. J. Evans; B. I. A. McInnes; L. M. Dent; I. O. H. Fielding (Australian Journal of Earth Sciences, 2023)

Can Ingoing Contact Chains and other cattle movement network metrics help predict herd-level bovine tuberculosis in Irish cattle herds? - Jamie A. Tratalos; Helen R. Fielding; Jamie M. Madden; Miriam Casey; Simon J. More (Preventive Veterinary Medicine, 2023)

Associations between biomarkers of cellular senescence and physical function in humans: observations from the lifestyle interventions for elders (LIFE) study - Roger A. Fielding; Elizabeth J. Atkinson; Zaira Aversa; Thomas A. White; Amanda A. Heeren; Sara J. Achenbach; Michelle M. Mielke; Steven R. Cummings; Marco Pahor; Christiaan Leeuwenburgh; Nathan K. LeBrasseur (GeroScience, 2022)
Cellular senescence is a plausible mediator of age-associated declines in physical performance. To test this premise, we examined cross-sectional associations between circulating components of the senescence-associated secretory phenotype (SASP) and measures of physical function and muscle strength in 1377 older adults. We showed significant associations between multiple SASP proteins and the short physical performance battery (SPPB), its subcomponents (gait speed, balance, chair rise time), and 400-m walk time. Activin A, ICAM1, MMP7, VEGFA, and eotaxin showed strong associations based on gradient boost machine learning (GBM), and, when combined with other proteins, effectively identified participants at the greatest risk for mobility disability (SPPB score $$\le$$ ≤ 7). Senescence biomarkers were also associated with lower grip strength, and GBM identified PARC, ADAMTS13, and RANTES as top candidates in females, and MMP2, SOST, and MCP1 in males. These findings highlight an association between senescence biomarkers and physical performance in older adults. ClinicalTrials.gov Identifier: NCT01072500.

Estimated Erosion from Clearcut Timber Harvests in the Southeastern United States - Jonah A H Fielding; Brent S Hawks; W Michael Aust; M Chad Bolding; Scott M Barrett (Forest Science, 2022)
Timber harvests with inadequate forestry best management practices (BMPs) can accelerate soil erosion, which has been associated with reductions in water quality and site productivity. Previous studies affirm positive water quality effects accrued by harvesting with BMPs. However, few studies document erosion rates and masses associated with harvest and access network features (e.g., decks, roads, skid trails, stream crossings) across different southeastern regions. This research evaluated 109 recent harvests across eleven southeastern states and three topographically different regions (Coastal Plain, Piedmont, and Mountains). Descriptive statistics of erosion for harvests and access features were developed from USLE-Forest model estimates. Harvests and access network areas were used in conjunction with erosion averages to calculate total erosion masses. Across the southeast, combined network features averaged nearly 12% of total harvest area yet produced approximately 48% of total site erosion due to disproportionately higher erosion rates. Regional differences indicated that the Mountain region had an average overall erosion rate of 6.8 t/ac/yr, whereas the Piedmont and Coastal Plain sites had lower average erosion rates of 2.7 and 2.2 t/ac/yr, respectively. Results suggest that additional BMP implementation strategies may be beneficial for erosion control from roads, skid trails, and stream crossings, particularly in erosive landscapes.

Estimating the average distribution of Antarctic krill Euphausia superba at the northern Antarctic Peninsula during austral summer and winter - V. Warwick-Evans; S. Fielding; C. S. Reiss; G. M. Watters; P. N. Trathan (Polar Biology, 2022)
This study was performed to aid the management of the fishery for Antarctic krill Euphausia superba . Krill are an important component of the Antarctic marine ecosystem, providing a key food source for many marine predators. Additionally, krill are the target of the largest commercial fishery in the Southern Ocean, for which annual catches have been increasing and concentrating in recent years. The krill fishery is managed by the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR), which has endorsed a new management framework that requires information about the spatial distribution and biomass of krill. Here, we use krill density estimates from acoustic surveys and a GAMM framework to model habitat properties associated with high krill biomass during summer and winter in the northern Antarctic Peninsula region, an area important to the commercial fishery. Our models show elevated krill density associated with the shelf break, increased sea surface temperature, moderate chlorophyll-a concentration and increased salinity. During winter, our models show associations with shallow waters (< 1500 m) with low sea-ice concentration, medium sea-level anomaly and medium current speed. Our models predict temporal averages of the distribution and density of krill, which can be used to aid CCAMLR’s revised ecosystem approach to fisheries management. Our models have the potential to help in the spatial and temporal design of future acoustic surveys that would preclude the need for modelled extrapolations. We highlight that the ecosystem approach to fisheries management of krill critically depends upon such field observations at relevant spatial and temporal scales.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

A framework for modelling soil structure dynamics induced by biological activity - Katharina Meurer; Jennie Barron; Claire Chenu; Elsa Coucheney; Matthew Fielding; Paul Hallett; Anke M. Herrmann; Thomas Keller; John Koestel; Mats Larsbo; Elisabet Lewan; Dani Or; et al. (Global Change Biology, 2020)
Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Oceanographic barriers, divergence, and admixture: Phylogeography and taxonomy of two putative subspecies of short‐finned pilot whale - Amy M. Van Cise; Robin W. Baird; Charles Scott Baker; Salvatore Cerchio; Diane Claridge; Russell Fielding; Brittany Hancock‐Hanser; Jacobo Marrero; Karen K. Martien; Antonio A. Mignucci‐Giannoni; Erin M. Oleson; Marc Oremus; et al. (Molecular Ecology, 2019)
Genomic phylogeography plays an important role in describing evolutionary processes and their geographic, ecological, or cultural drivers. These drivers are often poorly understood in marine environments, which have fewer obvious barriers to mixing than terrestrial environments. Taxonomic uncertainty of some taxa (e.g., cetaceans), due to the difficulty in obtaining morphological data, can hamper our understanding of these processes. One such taxon, the short‐finned pilot whale, is recognized as a single global species but includes at least two distinct morphological forms described from stranding and drive hunting in Japan, the “Naisa” and “Shiho” forms. Using samples ( n = 735) collected throughout their global range, we examine phylogeographic patterns of divergence by comparing mitogenomes and nuclear SNP loci. Our results suggest three types within the species: an Atlantic Ocean type, a western/central Pacific and Indian Ocean (Naisa) type, and an eastern Pacific Ocean and northern Japan (Shiho) type. mtDNA control region differentiation indicates these three types form two subspecies, separated by the East Pacific Barrier: Shiho short‐finned pilot whale, in the eastern Pacific Ocean and northern Japan, and Naisa short‐finned pilot whale, throughout the remainder of the species' distribution. Our data further indicate two diverging populations within the Naisa subspecies, in the Atlantic Ocean and western/central Pacific and Indian Oceans, separated by the Benguela Barrier off South Africa. This study reveals a process of divergence and speciation within a globally‐distributed, mobile marine predator, and indicates the importance of the East Pacific Barrier to this evolutionary process.

From intrabasinal volcanism to far-field tectonics: causes of abrupt shifts in sediment provenance in the Devonian–Carboniferous Drummond Basin, Queensland - K. Sobczak; S. E. Bryan; C. R. Fielding; M. Corkeron (Australian Journal of Earth Sciences, 2019)

Meta-analysis identifies mitochondrial DNA sequence variants associated with walking speed - Todd M. Manini; Thomas W. Buford; John A. Kairalla; Mary M. McDermott; Carlos A. Vaz Fragoso; Roger A. Fielding; Fang-Chi Hsu; Neil Johannsen; Stephen Kritchevsky; Tamara B. Harris; Anne B. Newman; Steven R. Cummings; et al. (GeroScience, 2018)

Probabilistic flood risk analysis considering morphological dynamics and dike failure - J. Oliver; X. S. Qin; O. Larsen; M. Meadows; M. Fielding (Natural Hazards, 2018)

Executive Dysfunction in Female FMR1 Premutation Carriers - Annie L. Shelton; Kim M. Cornish; Claudine M. Kraan; Reymundo Lozano; Minh Bui; Joanne Fielding (The Cerebellum, 2016)

The tectonic significance of lower Permian successions in the Texas Orocline (Eastern Australia) - M. Campbell; G. Rosenbaum; U. Shaanan; C. R. Fielding; C. Allen (Australian Journal of Earth Sciences, 2015)

Longitudinal decline of lower extremity muscle power in healthy and mobility-limited older adults: influence of muscle mass, strength, composition, neuromuscular activation and single fiber contractile properties - Kieran F. Reid; Evan Pasha; Gheorghe Doros; David J. Clark; Carolynn Patten; Edward M. Phillips; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2014)

Identification of serum analytes and metabolites associated with aerobic capacity - Michael S. Lustgarten; Lori Lyn Price; Tanya Logvinenko; Christos Hatzis; Nandan Padukone; Nicholas V. Reo; Edward M. Phillips; Dylan Kirn; John Mills; Roger A. Fielding (European Journal of Applied Physiology, 2013)

Cold-water carbonate deposition in a high-latitude, glacially influenced Permian seaway (Southern Carnarvon Basin, Western Australia) - T. D. Frank; J. M. Pritchard; C. R. Fielding; A. J. Mory (Australian Journal of Earth Sciences, 2012)

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

A transposon insertion single-gene knockout library and new ordered cosmid library for the model organism Streptomyces coelicolor A3(2) - L. T. Fernández-Martínez; R. Del Sol; M. C. Evans; S. Fielding; P. R. Herron; G. Chandra; P. J. Dyson (Antonie van Leeuwenhoek, 2011)

Distribution, growth, diet and foraging behaviour of the yellow‐fin notothen Patagonotothen guntheri (Norman) on the Shag Rocks shelf (Southern Ocean) - M. A. Collins; R. S. Shreeve; S. Fielding; M. H. Thurston (Journal of Fish Biology, 2008)
The distribution, total length ( L T ) frequency and diet of Patagonotothen guntheri are described from 14 bottom trawl surveys conducted on the Shag Rocks and South Georgia shelves in the austral summers from 1986 to 2006. Patagonotothen guntheri (80–265 mm L T ) were caught on the Shag Rocks shelf from depths of 111 to 470 m, but no specimens were caught on the South Georgia shelf. Multiple cohorts were present during each survey and L T ‐frequency analysis of these cohorts suggests that growth was slow (von Bertalanffy K = 0·133). Evidence from stomach contents and acoustic data (2005 and 2006) showed that P. guntheri is primarily a pelagic feeder, migrating from the sea floor towards the surface to feed during daylight. The diet of smaller fish ( Rhincalanus gigas , whilst larger fish principally consumed the pelagic hyperiid amphipod, Themisto gaudichaudii and Antarctic krill Euphausia superba . Some larger fish also took benthic prey.

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

A genome-wide scan for primary open-angle glaucoma (POAG): the Barbados Family Study of Open-Angle Glaucoma - Barbara Nemesure; Xiaodong Jiao; Qimei He; M. Cristina Leske; Suh-Yuh Wu; Anselm Hennis; Nancy Mendell; Joy Redman; Henri-Jean Garchon; Richa Agarwala; Alejandro A. Schäffer; Fielding Hejtmancik; et al. (Human Genetics, 2003)

Relationship of Pharmacokinetically-Calculated Volumes of Distribution to the Physiologic Distribution of Liposomal Drugs in Tissues: Implications for the Characterization of Liposomal Formulations - Robert M. Fielding (Pharmaceutical Research, 2001)

Safety, Toxicokinetics and Tissue Distribution of Long-Term Intravenous Liposomal Amphotericin B (ambisome®): A 91-day Study in Rats - Ihor Bekersky; Garry W. Boswell; Richard Hiles; Robert M. Fielding; Donald Buell; Thomas J. Walsh (Pharmaceutical Research, 2000)

A 5-base insertion in the γC-crystallin gene is associated with autosomal dominant variable zonular pulverulent cataract - Zhaoxia Ren; Anren Li; Barker S. Shastry; Tirunilai Padma; Radha Ayyagari; Mark H. Scott; Marshall M. Parks; Muriel I. Kaiser-Kupfer; J. Fielding Hejtmancik (Human Genetics, 2000)

A 5-base insertion in the γC-crystallin gene is associated with autosomal dominant variable zonular pulverulent cataract - Zhaoxia Ren; Anren Li; Barker S. Shastry; Tirunilai Padma; Radha Ayyagari; Mark H. Scott; Marshall M. Parks; Muriel I. Kaiser-Kupfer; J. Fielding Hejtmancik (Human Genetics, 2000)

Safety and Toxicokinetics of Intravenous Liposomal Amphotericin B (AmBisome ®) in Beagle Dogs - Ihor Bekersky; Garry W. Boswell; Richard Hiles; Robert M. Fielding; Donald Buell; Thomas J. Walsh (Pharmaceutical Research, 1999)

Altered Tissue Distribution and Elimination of Amikacin Encapsulated in Unilamellar, Low-Clearance Liposomes (MiKasome®) - Robert M. Fielding; Ramilla O. Lewis; Lotus Moon-McDermott (Pharmaceutical Research, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Role and management of donkeys in samburu and turkana pastoralist societies in Northern Kenya - M. Twerda; D. Fielding; C. Field (Tropical Animal Health and Production, 1997)